Instalation of a STD education program for the community of moinho slumof São Paulo– SP, Brazil - Strazza, Leila; Boccia, Tânia MQR; Carvalho, Heráclito B (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Introduction: This papeer aims at the search for a desirable solution against STD. Objective: identifying sexual risky behaviors and working for itsprevention. Methods: at the end of 2003 and the first semester of 2004 a preventive program with poor women from Moinho slum community wascarried out. A face to face questionnaire was applied. Two focal groups and three workshops were conducted by two psychologists. Results:the sam-ple participants aged between 20 and 54 years old; all of them had children, 72.4% had more than five kids; 86.2% were single; 72.4% consisted of29 elementary school, 21.7 were illiterate; 55.2 % collect garbage and recycle it, 65.5% had syphilis, 34.5% did not know the name of the diseasethey had. Lack of confidence in their sexual partners is demonstrated in the drawing call “the face of aids”, in wich nine women said it was their part-ner’s penis. Conclusion:these women who live in extreme poverty in a very large city like São Paulo do not realize the not risk of DST transmission. Key words: STD, disadvantaged women, slum, focal group, workshop, educational program.ARTIGOARTICLE1Pesquisadora Doutora da Faculdade de Medicina, Universidade de São Paulo – FMUSP2Psicóloga da Faculdade de Medicina, Universidade de São Paulo – FMUSP 3Professor Doutor, Departamento de Medicina Preventiva da Faculdade de Medicina,Universidade de São Paulo – FMUSP 4.